PELAYANAN PERUSAHAAN DAERAH AIR MINUM DI KCAMATAN MELIAU KABUPATEN SANGGAU - E.01108143, Elisabet (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The writing of this research is aimed to give a definition about Region firm Service Drinking Water at Meliau's district hit customer complaint hit service quality that is given, about problem distribution water that insufficiently smooth and frequent experiences jamming water, notably customer at Meliau's District, via this paper writing also intended, that ministering application process that qualified continually been done and improved by up to prima quality, so Region firm customer Drinking Water perceives service that is given really satisfies and no bad image of service facet especially Region firm customer Drinking Water that ranges three things:Transparation: open minded service,easy and can be access,available and understandable by everyone. accountability; it means could be responsible based on the rules of te laws.there is stability between rights and obligation. It means the service have a justice aspect between sender and recipient.Â Key words: Water Distribution Service. transparation of service, accountability of service, Â stability between rights and obligation.